Beginning iOS Application Development with HTML and JavaScript - Wagner, Richard 1966- (John Wiley & Sons, 2012)
Web developers with HTML/JS skills will quickly learn to apply them to the iPhone/iPad platformBeginning to intermediate web developers who want to apply their existing HTML/CSS/JS/Ajax skills to the wildly popular iPhone/iPad OS will love this book. In the highly successful Wrox Beginning format, it enables developers who know these core technologies to use what they already know and get up to speed quickly. It introduces iOS development with web technologies, explains how to enable and optimize web sites for the iPhone and iPad, explores user interface design, then moves into animation, spec.
Designing for Long Navigation Lists. - Print version record
Keywords: iOS (Electronic resource); iPhone (Smartphone) -- Programming; iPad (Computer) -- Programming; HTML (Document markup language); JavaScript (Computer program language); Application software -- Development; IOS (Electronic resource); iPhone (Téléphone intelligent); Programmation; iPad (Ordinateur); Programmation; HTML (Langage de balisage); JavaScript (Langage de programmation); Logiciels d'application; Développement; HTML; COMPUTERS; Programming; Microsoft Programming; Application software; Development